Analisis Perusahaan Sharp Electronics - Antony Sentoso; Jason Jason; Jesty Jesty; Deviana Deviana; Nancy Nancy; Hendro Hendro (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to analyze the implementation of good Corporate Social Responsibility (CSR) and Green Human Resources Management in the Sharp Electronics company. The main focus of the research is to understand how Sharp Electronics integrates corporate social responsibility and sustainable human resource management to achieve sustainable and environmentally friendly business practices. The results showed that Sharp Electronics has shown a strong commitment to social and environmental aspects through various CSR initiatives. Sharp Electronics' success in implementing CSR and GHRM has had a positive impact on the company's image, increased employee engagement, and created long-term business sustainability. As such, this research provides an in-depth insight into the CSR and GHRM practices at Sharp Electronics, which can provide inspiration and learning for other companies in their efforts towards better sustainability and social responsibility.